Formation of smectic phases in binary liquid crystal mixtures with a huge length ratio - Kapernaum, Nadia; Knecht, Friederike; Hartley, C. Scott; Roberts, Jeffrey C.; Lemieux, Robert P.; Giesselmann, Frank (Beilstein Journal of Organic Chemistry, 2012)
A system of two liquid-crystalline phenylpyrimidines differing strongly in molecular length was studied. The phase diagram of these two chemically similar mesogens, with a length ratio of 2, was investigated, and detailed X-ray diffraction and electrooptical measurements were performed. The phase diagram revealed a destabilization of the nematic phase, which is present in the pure short compound, while the smectic state was stabilized. The short compound forms smectic A and smectic C phases, whereas the longer compound forms a broad smectic C phase and a narrow higher-ordered smectic phase. Nevertheless, in the mixtures, the smectic C phase is destabilized and disappears rapidly, whereas smectic A is the only stable phase observed over a broad concentration range. In addition, the smectic translational order parameters as well as the tilt angles of the mixtures are reduced. The higher-ordered smectic phase of the longer mesogen was identified as a smectic F phase.
Keywords: bidispersity; liquid crystals; phase diagrams; smectic phases; smectic F phase; structure and dynamics